Properties of Silicon Dioxide Amorphous Nanopowder Produced by Pulsed Electron Beam Evaporation - Vladislav G. Il’ves; Michael G. Zuev; Sergey Yu. Sokovnin (Journal of Nanotechnology, 2015)
SiO2 amorphous nanopowder (NP) is produced with the specific surface area of 154 m2/g by means of evaporation by a pulsed electron beam aimed at Aerosil 90 pyrogenic amorphous NP (90 m2/g) as a target. SiO2 NP nanoparticles showed improved magnetic, thermal, and optical properties in comparison to Aerosil 90 NP. Possible reasons of emergence of d0 ferromagnetism at the room temperature in SiO2 amorphous NP are discussed. Photoluminescent and cathode luminescent properties of the SiO2 NP were investigated.